1969
DOI: 10.1126/science.164.3887.1519
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Sialoprotein

Abstract: The high content of sialic acid in the glomerulus is associated with the cell membrane of epithelial cells lining the basement membrane. Whereas enzyme studies indicate that sialic acid is a determinant of the nephritogenic antigen, the physicochemical properties of this nephritogenic glycoprotein suggest that sialic acid may have an important role in the filtration mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(54 citation statements)
references
References 21 publications
1
53
0
Order By: Relevance
“…Loss of such fixed negative charges has also been shown to be associated with proteinuria in several experimental glomerular diseases (2,3,7,31,32). Although anionic sites occur on the surfaces of both endothelium and epithelium (6,17,23,24,(31)(32)(33)43), the available evidence indicates that the GBM serves as both the charge and the size barrier in the filtration of macromolecules since all anionic proteins or neutral particles used as tracers (anionic ferritin [12,37], endogenous albumin [39], catalase [40], and neutral dextrans of varying size [55-78 A,] (5, 10)) do not penetrate beyond the LRI under normal flow conditions. The role of the GBM as the charge barrier was demonstrated directly by the experiments of Rennke et al (36,37) which showed that ferritin penetrates the GBM in increasing amounts the greater the isoelectric point.…”
Section: Possible Functions Of the Anionic Sitesmentioning
confidence: 99%
“…Loss of such fixed negative charges has also been shown to be associated with proteinuria in several experimental glomerular diseases (2,3,7,31,32). Although anionic sites occur on the surfaces of both endothelium and epithelium (6,17,23,24,(31)(32)(33)43), the available evidence indicates that the GBM serves as both the charge and the size barrier in the filtration of macromolecules since all anionic proteins or neutral particles used as tracers (anionic ferritin [12,37], endogenous albumin [39], catalase [40], and neutral dextrans of varying size [55-78 A,] (5, 10)) do not penetrate beyond the LRI under normal flow conditions. The role of the GBM as the charge barrier was demonstrated directly by the experiments of Rennke et al (36,37) which showed that ferritin penetrates the GBM in increasing amounts the greater the isoelectric point.…”
Section: Possible Functions Of the Anionic Sitesmentioning
confidence: 99%
“…Sialyl residues have been found in all three layers of the capillary wall. They have been detected in isolated glomerular basement membranes (GBM) (8)(9)(10) and in association with the cell membranes of both the endothelium (11)(12) and epithelium (4)(5)(6)(7)11), where they are part of the sialic acid-rich, cell-surface coats. A colloidal iron-stainable, cell-coat material is particularly concentrated on the epithelium.…”
mentioning
confidence: 99%
“…As far as the negative biochemical results are concerned, the explanation may lie in the fact that previous analyses for uronic acid (8,9) or sulfate groups (8) have been done on isolated GBM prepared by sonication, which, according to our experience, disrupts the anionic sites or, if prolonged, removes them entirely. Previous histochemical studies had the disadvantage that they were done on fixed sections (4)(5)(6)(7)(11)(12) incubated in basic dyes (with and without prior enzyme digestion). In such preparations it was difficult to make a clear distinction between the charged sites in the laminae rarae and those on the adjacent endothelial and epithelial cell membranes.…”
mentioning
confidence: 99%
“…More recently Shibata et al [47,48] demonstrated that the soluble supernatant obtained from trypsin-digested rat kidney homogenate has the capacity to stimulate the production of nephrotoxic antiserum in rabbits. Furthermore, Mohos and Skoza [40] recently reported that sialic acid is contained in the antigenic determinant of the nephritogenic antigen. These authors demonstrated that neuraminidase treatment of rat glomeruli greatly reduced the capacity of glomeruli to remove the .…”
Section: Introductionmentioning
confidence: 99%